A British Childhood? Some Historical Reflections on Continuities and Discontinuities in the Culture of Anglophone Childhood - Jarvis, Pam (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book considers how adults attempt to socialise young children into the adults it aspires to produce, from a number of diverse perspectives. The evolution of storytelling and its impact upon child development is initially explored, followed by the consideration of how social class, ethnicity, culture, and colonialism impact upon the ways that societies 'school' children about what to expect from adulthood. Different perspectives of early years education and growing up within a British/British colonial perspective are discussed and analysed. There is a focus throughout upon the way that children are constructed by the society in question, particularly those who are considered to be of lower status in terms of being poor, orphaned, or from ethnic groups against which the dominant culture discriminates. Topics covered by the chapters include topics covered by this Special Issue: current and historical constructions of childhood; the development of linguistic and 'storying' skills in childhood; childhood play and recreation; childhood and 'folk' narratives; philosophies of childhood; childhood and industrialisation; childhood and post-industrialisation; childhood education; childhood health; and cultures of childcare.